Financial and partnership independence : a missiological study of the partnership relationships in the Reformed church in Zambia (RCZ) 1966-2016 - Mbewe, Penias (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.